The effectiveness of antenatal class towards improvement of knowledge among pregnant women in Hospital Chancellor Tuanku Muhriz (HCTM) - Rohani Mamat; Roziah Arabi; Hartini Jantan; Hanisah Zainal Abidin; Nor Azizah Ahmad; Shakinah Awang (Malaysian Journal of Medicine and Health Sciences, 2020)
Antenatal knowledge is associated with positive outcome for pregnant women as it provides information to allow them to identify any problems during pregnancy. Studies have underlined the problems of the information overload is possible during an antenatal class, it is unclear to what extend information given during antenatal class are retain by mother, thus the need for this study. Methods: This is a quasi-pre-post experimental study involving 82 participants. Baseline pre and post knowledge on antenatal class was evaluated among respondents using validate questionnaires. T-test was used to determine the relationship between various socio-demographic factors and knowledge of respondents. Results: Chi-square test used to test pre and post knowledge score. There was a significant increase in the difference between before and after antenatal classes run against the knowledge. In addition, the study found no significant difference for participants who are professional and non-professional and level of education. Conclusion: This study concludes that the antenatal classes run in HCTM shows a positive impact in improving maternal care during pregnancy, childbirth and care after birth. It is best to suggest that to increase promotion and information regarding antenatal classes so that pregnant women and couple could attend and get the benefit from the class.